Poverty Reduction In Bojonegoro Regency Based On Regional Autonomy Implementation - Febrianti, Elika; Sutrisno, Sutrisno (Jurnal Mamangan, 2023)
Poverty Becomes a must problem quick completed , where problem poverty in the District Bojonegoro still many occur especially in regions with difficult access for reached. There is autonomy area (OTODA) is expected could strengthen power competitive with consider potential and diversity Indonesian region , as well democracy , equity , and justice , as well privileges and specialties. So that study this aim for review effectiveness application autonomy area to level poverty in the District Bojonegoro . Method research used is a mix of methods that is qualitative descriptive and quantitative equality regression . Research results this explain that Policy used in countermeasures poverty that exists in society is at level or level certain in accordance with criteria poverty experienced by the community . Government Regency Bojonegoro in To do countermeasures poverty To do cooperation with TNP2K (National Team for Management and Management poverty ). Decline poverty this no regardless with role government in take policy or use authority for welfare . As perpetrator in activity economy , society related tightly with achievements or deep targets growth economy . In accordance with results equality regression state that in the simultaneous test poverty influential significant on growth economy.. Based on conditions Regency Bojonegoro moment this accompanied with take into account strengths , opportunities , challenges , and more problems big that will faced in the future . Realization sustainable development is the main spirit that underlies it development area districts Bojonegoro in a manner evenly.